Modelling an improved power factor of a single phase rectifier for electric car battery charging application: article / Mohd Sobri Ibrahim - Ibrahim, Mohd Sobri
The awareness of cleaner environment has lead to the intensity use of electric machine and battery has been developed to be used intensely in motor vehicle. For this situation, a paper for modeling a high power factor (PF) and low ripple factor (RF) for electric vehicle battery charging application has been proposed. The single stage high power factor converter will be proposed in this paper.